The Role Of The Constitutional Judiciary In Conforming Legislation And Strengthening Federal Rule - El-Ghawati, Mohamed (Journal of Legal and Political Studies, 2025)
Constitutional Courts Have Become A Cornerstone Of The Constitutional System In Federal States. As Independent Institutions Distinct From Both Political And Judicial Bodies, Their Primary Function Is To Safeguard The Supremacy Of The Constitution. Rooted In The Theory Of The Rule Of Law, As Formulated By The Austrian Jurist Hans Kelsen, These Courts Provide Dual Protection. On The One Hand, They Ensure The Integrity Of The Constitutional Framework That Governs The Functioning Of Political Authority, Including The Federal Government And Its Relations With State Governments. In Fact, They Protect The Fundamental Legislation Of Regional Entities, Which Are Often Represented On The Basis Of Equality. The Federal Constitution Delineates The Process For Electing Or Appointing Representatives Within These Bodies And Defines Their Powers And Jurisdictions. The Main Objective Is To Enact Laws And Legislation Through A Process Of Consensus, Ensuring That The Legal Provisions Established Are Impartial And Do Not Favor One Group At The Expense Of Another. Additionally, It Aims To Safeguard The Fundamental Legislative Frameworks Of Various Regions, Which Are Predominantly Represented On The Basis Of Equality. Furthermore, The Federal Constitution Delineates The Procedures For Electing Or Appointing Representatives Within These Regions And Defines Their Respective Powers And Jurisdictions. The Primary Objective Is To Enact Laws And Legislation Through A Consensual Process, Ensuring That The Laws Issued Are Notbiased In Favor Of One Group At The Expense Of Another's Rights. It Serves As One Of The Key Safeguards That Uphold The Effectiveness Of The Federal System. The Establishment Of A Constitutional Court Is A Crucial Requirement, Ensuring That The Federal Government Possesses A Judicial Body Dedicated To Resolving Jurisdictional Conflicts. This, In Turn, Strengthens And Supports The Federal System, Which Is Considered The Most Democratic Framework Due To Its Capacity To Respond Effectively To Local Specificities. To Ensure Legislative Independence, It Is Essential That Each State Maintain A Legislative Body Or Local Parliament Responsible For Drafting State Legislation And Issuing Necessary Legislative Decisions. These Actions Must Align With The Requirements Of Both The Federal Constitution And The State Constitution, While Remaining In Harmony With The Prevailing Political, Economic, And Social Conditions. Such Provisions Are Typically Mandated In Most Federal Constitutions. Keywords: Federal System-The Constitutional Court - dispute resolution - constitutional authorities─ Interpretation
Keywords: Federal SystemThe Constitutional Court dispute resolution constitutional authorities Interpretation